4CPS-108 Patient and physicians's satisfaction with clinical pharmacy services on a haematology ward in a large tertiary care hospital. Issue 1 (23rd March 2023) - Neefs, J; Simons, E; Janssens, A; Spriet, I; Van Nieuwenhuyse, T
Abstract : Background and Importance: Oral anticancer therapy is increasingly used for the treatment of hematologic malignancies. Despite its convenience, several challenges such as medication adherence may impact therapeutic effectiveness and outcome. Therefore, a clinical pharmacy service was initiated on the haematology ward at our hospital . Aim and Objectives: To determine the satisfaction rate of the clinical pharmacy service in patients with haematological malignancies treated with oral anticancer therapy and in haematologists-in-training. Material and Methods: Between January and May 2022, a survey was developed to assess patient and haematologists-in –training satisfaction and perceived value of healthcare services provided by clinical pharmacists at a tertiary care hospital. The survey was taken by a pharmacist not involved in daily clinical pharmacy practice. The survey contained questions addressing demographic, type of oral anticancer therapy and pharmacist-specific items. Responses were analysed using descriptive statistics. Satisfaction was assessed by 5 Likert-scale questions and either 8 or 4 open-ended questions for cancer patients and for haematologists in training, respectively. We aimed to have a satisfaction rate of at least 80%. Results: A total of 65 patients and 11 haematologists-in-training participated in the survey. All patients (100%) ranked the pharmacists' explanation about medication intake and side-effects as either very satisfying or satisfying . Counselling about drug interactions was the only criterion that did not result in the achievement of the predefined 80% satisfaction rate, with 27.6% of patients being very satisfied and 51.7% of patients being satisfied about this topic, respectively. Overall, the majority of patients (89.7%) indicated that pharmacist counselling and follow-up visits were of added value. All 11 included haematologists in training expressed high levels of satisfaction with the clinical pharmacist service. Conclusion and Relevance: High levels of satisfaction with the clinical pharmacist service was reported by both patients with a haematological malignancy and haematologists-in-training. This survey identified that counselling on drug interactions of oral cancer therapy might be improved. Further studies may include assessment of the association between patient satisfaction and compliance and treatment outcomes. Also the added value and cost effectiveness of the clinical pharmacist service needs to be investigated in future research. References and/or Acknowledgements: Conflict of Interest: No conflict of interest